Emerging trends in communication networks - Hasan, Syed Faraz (SpringerBriefs in Electrical and Computer Engineering, 2014)
This book covers the state of the art in communication networks with the help of illustrative diagrams and recent references published in reputed journals and magazines. The book gives readers a glimpse into the next generation of communication networks. It explores topics that are currently in the research phase and/or are expected to be deployed in recent future such as LTE networks and IPv6 networks. This book is written for students/researchers who wish to come up to date with the recent trends in telecommunications.